Numerical Investigation into the Distributor Design in Radial Flow Adsorber (Advances in Applied Mathematics and Mechanics, 2021)
Air flow distribution in radial flow adsorber was numerically investigated using computational fluid dynamics (CFD) method, which was proved to be applicable to study the problem of non-uniform distribution in radial flow adsorber. Results showed that the degree of non-uniformity was more serious in desorption process than that is adsorption process. Therefore, it was considered that the non-uniform distribution of flow in a radial flow adsorber was mainly manifested in the desorption process. Optimum design of distributor parameters can improve the flow distribution in adsorber. Meanwhile, three different structures of distributor and the effect of breathing valve were analyzed. Results revealed that truncated cone is more effective than tubular and conical distributors in flow distribution. By inserting the truncated cone in central channel, desorption uniformity was increased by 6.56% and the breakthrough time of CO$_2$ was extended from 564s to 1138s in the adsorption process. The "dead zone" problem at the top of adsorber during the desorption process was solved by opening breathing valve, which prolonged the working life of adsorber and was proved to have less effect on the uniform of airflow.